(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
This article addresses the dialectical relationship between reality and myth in the poetry of Mahmoud Darwish, considering it as both an artistic and visionary tool that enabled the poet to transcend the limitations of the historical moment toward a universal human horizon. Darwish employed myth not as a static heritage, but rather as a symbolic energy that he reshaped according to the requirements of his poetic and political experience, thus endowing it with meanings of resistance, resurrection, and immortality. He utilized multiple mythological symbols such as the Phoenix, Tammuz, and the Odyssey to embody the Palestinian existential struggle between loss and rebirth. Through this mythic employment, Darwish succeeded in establishing a poetics in which myth intersects with reality, expressing a collective consciousness that seeks redemption and the restoration of the human meaning of life.